The effect of raffinose and methionine on frozen/thawed Angora buck (Capra hircus ancryrensis) semen quality, lipid peroxidation and antioxidant enzyme activities - Tuncer, Puerhan Barbaros; Bucak, Mustafa Numan; Sariozkan, Serpil; Sakin, Fatih; Yeni, Deniz; Cigerci, Ibrahim Hakki; Buyukleblebici, Olga (Academic Press Inc Elsevier Science, 2010)
The aim of the present study was to determine the effects of different doses of raffinose and methionine on post-thawed semen quality, lipid peroxidation and antioxidant enzyme activities of Angora buck (Capra hircus ancryrensis) sperm following cryopreservation. Ejaculates collected from three Angora bucks were evaluated and pooled at 37 degrees C. Semen samples, which were diluted with a Tris-based extender containing the additives raffinose (2.5, 5, 10 mM) and methionine (2.5, 5, 10 mM) and an extender containing no antioxidants (control), were cooled to 5 degrees C and frozen in 0.25 ml French straws. Frozen straws were thawed individually at 37 degrees C for 20 s in a water bath for evaluation. The freezing extender supplemented with 2.5 and 5 mM methionine led to higher percentages of CASA motility (63.6 +/- 7.0; 63.4 +/- 3.1%, respectively), in comparison to the controls (P < 0.01) following the freeze-thawing process. The addition of antioxidants did not provide any significant effect on the percentages of post-thaw subjective and CASA progressive motilities as well as sperm motion characteristics (VSL and VCL), compared to the control groups (P > 0.05). The freezing extender with raffinose (5 and 10 mM) and methionine at three different doses (2.5, 5 and 10 mM) led to lower percentages of acrosome abnormalities, in comparison to the controls (P < 0.001). In the comet test, raffinose (5 and 10 mM) and methionine (10 mM) gave scores lower than those of the controls, and thereby reduced DNA damage (P < 0.05). Malondialdehyde formation was found to be lower (1.8 +/- 0.1 nmol/L) in the group of 5 mM raffinose, compared to the controls following the freeze-thawing process (P < 0.01). The additives did not show any effectiveness on the maintenance of SOD, GSH-PX and GSH activities, when compared to the controls (P > 0.05). In conclusion, methionine and raffinose play a cryoprotective role against sperm CASA motility, acrosome abnormality and DNA damage. Raffinose 5 mM exhibited antioxidative properties, decreasing MDA levels. Further studies are required to obtain more concrete results on the characterization of microscopic parameters and antioxidant activities in cryopreserved goat sperm with different additives. Crown Copyright (C) 2010 Published by Elsevier Inc. All rights reserved.
Keywords: Angora buck semen; Antioxidants; Antioxidant activity; Cryopreservation; Sperm characteristics